Serum Markers of Bone Turnover and Angiogenesis in Bisphosphonate-related Osteonecrosis of the Jaw Patients Following Discontinuation of Long-term Intravenous Bisphosphonate Therapy - Thumbigere-Math, Vivek (J Oral Maxillofac Surg, 2015)
PURPOSE: To analyze serum markers of bone turnover, angiogenesis, endocrine function, and inflammation in bisphosphonate-related osteonecrosis of the jaw (BRONJ) patients who discontinued long-term intravenous bisphosphonate (BP) therapy. PATIENTS AND METHODS: Serum samples were obtained from 25 BRONJ patients who had discontinued long-term intravenous BP therapy for an average of 11.4±8.7 months and 48 non-BRONJ controls who continued receiving intravenous BP therapy. Samples were analyzed for total alkaline phosphatase (ALP), bone-specific alkaline phosphatase (BALP), osteocalcin (OCN), C-telopeptide (CTX), vascular-endothelial growth factor (VEGF), triiodothyronine (T3), thyroxine (T4), thyroid-stimulating hormone (TSH), 25-hydroxyvitamin D, and C-reactive protein (CRP). RESULTS: The mean number of BP infusions was significantly higher in BRONJ subjects compared with controls (38.4±26.3 infusions vs 18.8±7.2, p<0.0001); however, the duration of BP therapy was not significantly different between the groups (p=0.23). Overall, there were no significant differences in any of the markers between BRONJ subjects and controls (all p values ≥ 0.16). In a subgroup analysis that matched BRONJ subjects and controls according to mean age and BP infusions (BRONJ, n=10 and controls, n=48), log(10)VEGF (2.9±0.4 vs 2.4±0.4, p=<0.001) and CRP (34±26 vs 13±8, p=<0.01) levels were significantly higher in BRONJ subjects compared with controls. Within BRONJ subjects, none of the serum markers were correlated with duration of BP discontinuation. CONCLUSIONS: Bone turnover and endocrine markers in BRONJ subjects who discontinue long-term intravenous BP therapy are similar to non-BRONJ controls receiving intravenous BP therapy. However, angiogenesis and inflammation markers are higher in BRONJ subjects who discontinue long-term intravenous BP therapy. The prolonged skeletal half-life of BPs may suppress bone turnover markers in BRONJ subjects for several years following discontinuation of intravenous BP therapy, suggesting an extended effect on bone homeostasis.